2009
DOI: 10.1111/j.1552-6569.2008.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Laughing As a Manifestation in a Clinically Isolated Brainstem Syndrome: A Case Report

Abstract: The prevalence of pathological laughing and crying in multiple sclerosis (MS) is 10%. It has been speculated that the anatomical lesion responsible for the pathological laughing is located in the pontine base, prefrontal cortex, and cerebellum. We report an 18-year-old male patient presenting with pathological laughing and hypomania. In his neurological examination, he had a euphoric effect with ataxic walking and dysarthria speech. He had a bilateral conjugated gaze limitation, with a prominent bilateral hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…This analysis showed that compared with those without PLC, people with MS with PLC had fewer lesions in the posterior fossa when controlling for depressive symptoms. Compared with previous work implicating brainstem and cerebellum lesions in PLC, 2,12,13,20,21 the present results are not in line with the predicted hypothesis; however, they provide insight and further our understanding of the underpinnings of PLC. The present results suggest that lesion localization alone, specifically, in the posterior fossa, is insufficient to predict the development of PLC in people with MS.…”
Section: Discussioncontrasting
confidence: 99%
“…This analysis showed that compared with those without PLC, people with MS with PLC had fewer lesions in the posterior fossa when controlling for depressive symptoms. Compared with previous work implicating brainstem and cerebellum lesions in PLC, 2,12,13,20,21 the present results are not in line with the predicted hypothesis; however, they provide insight and further our understanding of the underpinnings of PLC. The present results suggest that lesion localization alone, specifically, in the posterior fossa, is insufficient to predict the development of PLC in people with MS.…”
Section: Discussioncontrasting
confidence: 99%
“…PLC in multiple sclerosis is the result either of isolated lesions to specific areas of the brain (in medulla oblongata and the mesencephalon [ 54 ], clinically isolated syndrome with pontine lesion [ 55 ]) or the consequence of an extensive diffuse involvement of the brain especially of the prefrontal cortex producing a complex neuropsychological impairment [ 56 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of PBA has been reported in a multitude of neurologic illnesses including, but not limited to, ALS, [15][16][17][18][19] PD and other movement disorders, 13,[20][21][22] MS, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] stroke, [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] various types of dementia and other neurodegenerative disorders, 55-62 traumatic brain injury (TBI), 63-66 central nervous system tumors, [67][68][69][70][71][72][73][74]...…”
Section: Epidemiologymentioning
confidence: 99%